Structure Of Islamic Religious Education Materials On Formal Education Pathways For Junior And High School Level In Indonesia - Teuku Hariski Munazar; Andi Prastowo (AIUA Journal of Islamic Education, 2020)
In general, religion has a very important role in human life; religion is also one that embodies life. Religious education adds spiritual potential and also shapes students to become human beings who believe in Allah SWT and have good morals. Increase the potential for spiritual understanding, and instil Islamic and religious values. type of qualitative research, namely through library research. This study supports the PAI material concept for SMP / MTs, SMA / MA data collection methods using the documentation method, carried out by analyzing the Ministry of Education Regulation No. 21 of 2016 and also taken from relevant books. Instead, Al-Qur'an, Hadith which is the main source in the teachings of Islam, then there are subjects of the Aqeedah which are very important to be discussed with students as roots or religion. There are fiqh lessons which are a set of rules that deliver human relations with God and other collections. And the last is the subject of Islamic history is the story of the journey of Muslim human life.